A Synthetic Glycopeptide Vaccine for the Induction of a Monoclonal Antibody that Differentiates between Normal and Tumor Mammary Cells and Enables the Diagnosis of Human Pancreatic Cancer. Issue 8 (22nd January 2016) - Palitzsch, Björn; Gaidzik, Nikola; Stergiou, Natascha; Stahn, Sonja; Hartmann, Sebastian; Gerlitzki, Bastian; Teusch, Nicole; Flemming, Peer; Schmitt, Edgar; Kunz, Horst
Abstract: In studies within the realm of cancer immunotherapy, the synthesis of exactly specified tumor‐associated glycopeptide antigens is shown to be a key strategy for obtaining a highly selective biological reagent, that is, a monoclonal antibody that completely differentiates between tumor and normal epithelial cells and specifically marks the tumor cells in pancreas tumors. Mucin MUC1, which is overexpressed in many prevalent cancers, was identified as a promising target for this strategy. Tumor‐associated MUC1 differs significantly from that expressed by normal cells, in particular by altered glycosylation. Structurally defined tumor‐associated MUC1 cannot be isolated from tumor cells. We synthesized MUC1–glycopeptide vaccines and analyzed their structure–activity relationships in immunizations; a monoclonal antibody that specifically distinguishes between human normal and tumor epithelial cells was thus generated. Abstract : Synthetic antitumor vaccines obtained by the coupling of MUC1 glycopeptides of varied sequence and glycosylation to a tetanus toxoid induce very strong immune responses in mice, but antibodies of distinctly different binding to tumor cells. From a mouse immunized with vaccine A, a monoclonal IgG1 antibody was generated that differentiates between normal und tumor human mammary cells and selectively recognizes the tumor cells in human pancreas tumor tissues.